Pathways Linking Parental Care and Control to Loneliness in Breast Cancer Patients with A History of Childhood Maltreatment: Exploring the Mediating Roles of Ambivalence Over Emotional Expression and Self-Discrepancy - Heshmati, Rasoul (Journal of interpersonal violence, 2024)
Childhood maltreatment is a risk factor for loneliness and is linked to breast cancer. Parental bonding experienced during one’s childhood also plays a significant role in increasing or decreasing the risk of loneliness later in life. Previous research has highlighted the significance of ambivalence over emotional expression (AEE) and self-discrepancy in the psychological adaptation of breast cancer patients, particularly concerning the impact of parental care and control experienced by patients in their relationship with their parents during childhood. Nevertheless, previous studies have not examined the mediating effects of AEE and self-discrepancy on parental care and control, as well as loneliness, in breast cancer patients. This study aimed to investigate whether AEE and self-discrepancy mediate the association of childhood parental care and control with loneliness in breast cancer patients with a history of childhood maltreatment. One hundred and thirty-three breast cancer patients who were receiving chemotherapy within the first 3 months post-diagnosis were recruited from one private and three public hospitals in Tabriz, Iran, to complete questionnaires. Parental bonding, loneliness, AEE, and self-discrepancy were assessed using the Parental Bonding Instrument (PBI), University of California Los Angeles (UCLA) Loneliness Scale, Ambivalence over the Expression of Emotion Questionnaire (AEQ), and Self-Discrepancies Scale (S-DS). Mediation models were tested using structural equation modeling. Effects of parental care (β = −.17, p < .05) and control (β = .21, p < .001) on loneliness were significant. Furthermore, both AEE (β = .19, p < .05) and self-discrepancy (β = .23, p < .01) significantly predicted loneliness. The pathway between parental care and AEE was significant (β = −.21, p < .001), as was the direct effect of parental control on self-discrepancy (β = .19, p < .05). Bootstrapping results showed that AEE significantly mediated the relationship between parental care and loneliness (95% confidence interval [CI] [−0.09, −0.01]). In addition, there was a significant indirect effect from parental control to loneliness via self-discrepancy (95% CI [0.11, 0.01]). These findings suggest that AEE and self-discrepancy could potentially be utilized in preventing or addressing loneliness in breast cancer patients who have a history of childhood maltreatment. Future research could, for example, assess whether integrating psychosocial interventions focusing on these variables as part of medical care can improve the mental health status of this subgroup of breast cancer patients who have experienced childhood maltreatment.